How Modern Markets See Web (or Internet) Space? - Boras, Damir (Array, 2004)
Nowadays everybody believes to have a quiet realistic picture of issue “ how modern markets see Web (short from World Wide Web) or Internet space” (?) and about someone’ s decision-making at the Web (or Internet) as a modern market place. Is it so? Maybe it is not so easy to know? Consequently our interest in this short scientific consideration is to research what are the real restrictions, rules, and regulations prevailing at the Web (or Internet) space as a modern market place. In this study we follow only the Web (or Internet) practice of modelling of someone’ s right decision-making at the Web (or Internet), thereby implementing in formal and informal terms about business understanding of the Web (or Internet) as a modern market place. In the same direction we can use some opposite business examples in which prevails negative business Web (or Internet) practice with some problems of profitability, also. The appropriateness of “ the independence from irrelevant alternatives” property is checked by referring to the relevant experimental business cases and practice. As in the case of usual modern market place (stock market and other markets) the well-known objection of the independence from irrelevant alternatives is not relevant, especially not when specifying the decision structure adequately. Only by reasons of profitability and by other positive business practice arguments we propose the best modelling practice of Web (or Internet) sub-markets realised by the application of positive practical models, something like: Web (or Internet) sub-markets certification, business modelling of right decision-making on Web (or Internet), ranking, etc.